2016
DOI: 10.5414/cn108902
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β promotes tubulointerstitial injury in 
MPO-ANCA-associated glomerulonephritis

Abstract: Sterile inflammation leads to the formation of ANCA-mediated neutrophil extracellular traps (NETs), which may stimulate macrophages and dendritic cells via TLR4 and induce NF-κB-dependent mRNA expression and translation of pro-IL-1β. Simultaneously, damage-associated molecular pattern signals resulting from NETs promote NLRP3 inflammasome-dependent processing and release mature active IL-1β. Sterile inflammation utilizing the NLRP3 inflammasome might be a characteristic reaction limited to the tubulointerstiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Afterwards, NF-κB stimulates macrophage infiltration of renal interstitium and the apoptosis of renal tubular cells by increasing the production of proinflammatory chemokines [ 18 ]. In order to investigate if NLRP3 inflammasome takes part in the development of tubulointerstitial inflammation and injury Tashiro et al assessed kidney biopsy specimens of 28 patients with TI [ 19 ]. Researchers discovered that IL-β1 was elevated in all samples and positively correlated with the severity of the tubulointerstitial injury.…”
Section: Role Of Nlrp3 In Pe and Pihmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, NF-κB stimulates macrophage infiltration of renal interstitium and the apoptosis of renal tubular cells by increasing the production of proinflammatory chemokines [ 18 ]. In order to investigate if NLRP3 inflammasome takes part in the development of tubulointerstitial inflammation and injury Tashiro et al assessed kidney biopsy specimens of 28 patients with TI [ 19 ]. Researchers discovered that IL-β1 was elevated in all samples and positively correlated with the severity of the tubulointerstitial injury.…”
Section: Role Of Nlrp3 In Pe and Pihmentioning
confidence: 99%
“…Researchers discovered that IL-β1 was elevated in all samples and positively correlated with the severity of the tubulointerstitial injury. Moreover, there was a positive correlation of NLRP3 mRNA with the severity of TI as well, which indicates that NLRP3 inflammasome is associated with TI and might contribute to its development [ 19 ]. As was described above, NLRP3 inflammasome activates not only IL-β1 and IL-18 but also gasdermin D, and Li et al reported that gasdermin D can lead to kidney injury through the induction of renal tubular cell pyroptosis in the course of treatment with cisplatin [ 20 ].…”
Section: Role Of Nlrp3 In Pe and Pihmentioning
confidence: 99%
“…In the Tokushima rat model, activation of NLRP3 inflammasomes accelerates macrophage recruitment and M1 polarization, promoting CXCL12 and high mobility group box-1 release in the proximal tubule, and contributing to the progression of diabetic nephropathy [ 49 ]. It is also observed clinically that NLRP3 inflammasomes are activated and mature IL-1β is released in anti-neutrophil cytoplasmic antibody-associated glomerulonephritis patients [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…TLR4 seems to be responsible for this kind of neutrophil activity in particular as many publications demonstrated their interaction via HMGB-1 [55], superoxide production [69], platelet activation [29] or IL-1β [70]. Oxidised low-density lipoprotein, which has been implicated as an independent risk factor in various acute or chronic inflammatory diseases including SIRS, was also found to act as a NETosis trigger via TLRs [71]. More recently, TLR9 has come into focus in NET research as mtDNA and other DAMPs that are recognised by TLR9 showed high potential to induce NETs in trauma patients [39], in liver ischemia/reperfusion injury [3] or due to surgical stress [72].…”
Section: Toll-like Receptorsmentioning
confidence: 99%